Trend of Non-Alcoholic Fatty Liver Disease in Type II Diabetes Mellitus - Fariha Khan; Umar Murad Khan; Ali Murad Khan; Usman Mir Khan (ziauddin University, 2024)
Background:  Non-alcoholic fatty liver disease (NAFLD) is becoming quite common in Type II Diabetes Mellitus (TIIDM) as obesity and insulin resistance are common within TIIDM and it is becoming a widespread liver condition globally. This study evaluated the prevalence of NAFLD patients who also had type II diabetes. Methods: The demographic data (name, age, body mass index (BMI), gender, occupation, duration of TIIDM, and treatment taking for TIIDM), as well as the results of the tests for these enzymes, were also recorded. Alanine transaminase (ALT) and Aspartate transaminase (AST) levels, as well as abdominal ultrasound findings of the liver, were recorded in a proforma after informed consent for a total of 200 Type II diabetic patients. Using SPSS, the data were analyzed, and stratified groups were subjected to the Chi-square tests. Results: There was a significant difference (p<0.05) observed in NAFLD patients of TIIDM concerning age, gender, BMI, treatment, occupation, and duration of diabetes. The sample size consisted of 200 patients of which 111 (55.5%) were men and 89 (44.5%) were women. Patients ranged in the age range of 40-70 years old, with a mean age of 55.08 ± 8.98 years and a mean BMI of 29.69±4.04, respectively. It was concluded that 64% of cases with diabetes mellitus had NAFLD. Conclusion: TIIDM is an independent risk factor for NAFLD so early screening, diagnosis, and appropriate treatment are mandatory to reduce the risk of NAFLD and its related complications.